Tenofovir and its potential in the treatment of hepatitis B virus - Laura Reynaud; Maria Aurora Carleo; Maria Talamo; Guglielmo Borgia (Dove Medical Press, 2009)
Laura Reynaud, Maria Aurora Carleo, Maria Talamo, Guglielmo BorgiaDepartment of Public Medicine and Social Security – Section of Infectious Disease University of Naples “Federico II”, ItalyAbstract: Recent literature is reviewed about treatment of chronic hepatitis B virus (CHB), focusing on tenofovir disoproxil fumarate (TDF; Viread®), among the nucleotide and nucleoside analogs. TDF pharmacokinetics and pharmacodynamics, activity in respect of hepatitis B virus (HBV) multi-drug-resistant mutations, efficacy in treatment-naïve and treatment-experienced patients, and side effects are described. The most predictive response factors to TDF therapy are discussed and all available combination therapies to optimize clinical outcome in the various patient profiles are analyzed, such as compensated and/or decompensated cirrhotic patients. The use of TDF in pregnancy, and prophylaxis after exposure to HBV and post-liver transplantation are also evaluated.Keywords: HBV, chronic hepatitis B, tenofovir, antiviral therapy